Liver injury following small intestinal ischemia reperfusion in rats is attenuated by Pistacia lentiscus oil: antioxidant and anti-inflammatory effects. (8th August 2017) - Saidi, Saber Abdelkader; Ncir, Marwa; Chaaben, Rim; Jamoussi, Kamel; van Pelt, Jos; Elfeki, Abdelfattah
Abstract: Context: Intestinal ischemia-reperfusion (IIR) not only leads to severe intestine damage but also induced subsequent destruction of remote organs. Objective: We investigated the protective effect of Pistascia lentiscus L. (Anacardiaceae) oil on IIR. Materials and methods: Wistar rats were divided into three groups: sham, intestinal IR and P. lentiscus pretreatment ( n  = 18 each). In the pretreatment group, oil was administered 1 h before induction of warm ischemia. Results: IIR led to severe liver damage manifested as a significant ( p  < .05) increase of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Pistacia lentiscus oil decreased the visible intestinal damage, as well as a significant decrease in serum AST and ALT levels. In addition, Pistacia lentiscus reduce liver injury, as evidenced by the decrease in liver tissue myeloperoxidase activity and lipoperoxidation (MDA) level. Conclusion: Pistascia lentiscus attenuates liver injury induced by IIR, attributable to the antioxidant and anti-inflammatory effect.